Principles of Entrepreneurship (ENT530): Social Media Portfolio: Muu's De Kitchen / Ummu Sobirah Mohd Rosli - Mohd Rosli, Ummu Sobirah (2021)
Muu’s De Kitchen is a food business collaboration between Ummu Sobirah and her sister Ummu Radhiyyah and have register the business under go-ecommerce. The business is conducted at residential area in No 19 Jalan EH 35 Taman Evergreen Height, 83000 Batu Pahat, Johor. Muu’s De Kitchen can be known as a local online business that sell assorted of Vietnamese Rolls and as our target to open our own restaurant that sell a healthy food and ithers. My business has 3 members which have their positions as manager, assistant, and runner for delivery. My main target audience are healthy food lover such as teenager, family and a group of people who are on diet and food hunter. I and my sister provide self-pickup, and cash on delivery. I believe that my online business will be growth and more successful with supported by our beloved customer. My business is focusing on product as well as creating values with the customers. I am strongly seeing the opportunities to success in this food and beverages business because the product itself have their own unique taste, freshness and varieties can satisfied people demand in the market. Vietnamese rolls is the food that can eat at anytime and anywhere. It is good for healthy food lover and acceptable to all age, gender and status. The price is affordable and from Muslim Halal product. It convince me if I and my sister work harder, our business will have a good place in the market and can achieve higher profit in the future.